Girls gone green - Hirshfield, Lynn (Puffin Books, 2010)
Everyone's going green these days, but saving the environment is a large task for anyone to take on, especially a teenager. The everyday green girls profiled here have a passion to do just that. They've stepped up, taken the initiative, and made their voices heard, and in doing so, they have helped to effect change. Filled with stories from real girls who made a difference, plus lots of celebrity green girls who are doing their part to help out, Girls Gone Green gives girls everywhere the inspiration to do something to help their world.